Strategi Analisis SWOT pada Pengembangan Website Pusat Studi: Dukungan Diseminasi Persebaran Informasi: SWOT Analysis Strategy in Developing Study Center Websites: Supporting the Dissemination of Information - Damayanti, Retno Wulan; Setiadi, Haryono; Laksono, Pringgo Widyo; Triyono, Joko (Technomedia Journal, 2025)
The Center for Research and Development of Technology and Industrial Collaboration, which is part of the Sebelas Maret University Research and Community Service Institute (PKPTKI LPPM UNS) in 2023, requires the development of an agency website for the dissemination and distribution of information to the public. The main objective is to provide information on research products and services that need to be promoted to the wider community. This website is expected to support the socialization of research results, PKPTKI member consultation services, and collaboration results and other activities. Through qualitative research using primary data obtained through Forum Group Discussion (FGD), this research produced a bilingual PKPTKI website. The SWOT (Strength, Weakness, Opportunity, Threat) analysis process was carried out through brainstorming activities with 4 members and 6 PKPTKI partners, and the results were used to map website needs, technical design and website content, and overall evaluation. The strategies resulting from the SWOT analysis involve developing a backend system to improve the PKPTKI website in English, scheduling consistent content updates, coordinating with the UNS ICT unit for website security, and preparing administrative SOPs for risk mitigation. The final result of this study is an effective PKPTKI website for widespread information dissemination and supporting interaction with various parties, including industry partners, practitioners, and national and international researchers.